Psycholinguistics in Meeting the Challenges of Advanced Aeromobility and Organizing Safe Air Traffic in Low-Altitude Aviation - Разіям Анаятова; Інна Рябченко; Гульназ Тулекова; Наталія Левченко; Абай Кошеков (Психолінгвістика)
The aim of the research is guided by the results of empirical research and naturalpsycholinguistic experiment, to assess the impact of the linguistic aspects use of the state language in civil aviation of the Republic of Kazakhstan on the challenges of future aeromobility and the organization of safe air traffic of low-altitude aviation.